PENANGANAN PRODUK DAN PACKAGING IKAN DENGAN PENDEKATAN GOOD MANUFACTURING PRACTICES - Gustiarini Rika Putri; Irna Ekawati; Pharmayeni; Haswan; Erwinsyah Sipahutar (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Fumigation is a method of processing or preserving by utilizing a combination of drying treatment and the application of natural chemical compounds from the combustion of natural fuels, so that the aroma and taste that is characteristic of smoked fish products and the color becomes golden or brown. Processing conditions can be improved by using the Good Manufacturing Process (GMP), standardizing starting from raw materials, supporting materials, processes to final products and applying the principles of good sanitation and hygiene. One of the applications of GMP in fish processing is good packaging of product, namely vacuum packaging. Vacuum packaging is a packaging method that removes air from the packaging before sealing / press. This method can be used manually or automatically such as inserting the product into a plastic vacuum bag, removing air from the plastic and sealing the plastic. Pesisir Selatan Regency is an area with vast marine potential, large fishery potential. Although there are many producers of dried fish, product handling is still inadequate. For this reason, as one form of community service from the ATI Padang Polytechnic community, a counseling and training was held on the Handling of Fish Products and Packaging with a Good Manufacturing Practices Approach in the Ampang Pulai Koto XI Tarusan.